COMPARATION OF POLYOLS AS CARBONIZING AGENTS OF FLAME RETARDANT INTUMESCENT TYPE COMPOSITIONS - VAKHITOVA, LIUBOV; KALAFAT, KONSTANTIN; TARAN, NADIYA; BESSARABOV, VOLODYMYR (Technologies and Engineering, 2022)
Purpose. To study the influence of the carbonizing agent structure on the formation of thermal insulating char layer of intumescent system acid donor/polyol and on the fire protection efficiency of the system at high temperatures. Methodology. A fire retardant mixture of an acid donor (phosphates ammonium, urea, melamine)/ polyol was chosen as a model intumescent system. Dispersion of vinyl acetate copolymer with ethylene was used as a polymeric component. The study applied the characteristics of the char layer of the intumescent composition at a certain temperature. The volumetric intumescent coefficient (K, cm3/g), mass of char residue (m, %), structure and density of the char layer are proposed as the main estimated parameters of flame retardant effect. IR spectroscopy was used to identify products of thermolysis of intumescent systems. Determination of fire protection efficiency of intumescent coatings was carried out in a mini-oven under standard fire conditions. Findings. The influence of polyol structure on the formation of thermal insulating char layer of intumescent acid donor/polyol system and the prediction of fire protection efficiency of this system under high temperature conditions has been investigated. It has been shown that under conditions of thermal shock the fire protection efficiency is more dependent on the nucleophilic reactivity of the polyol towards the unsaturated phosphorus atom of the acid donor than on its thermal stability. It has been found that pentaerythritol, dipentaerythritol, starch, dextrin, xylitol and sorbitol are the most effective carbonizing agents, regardless of the structure of the acid donor. It has been proved by infrared spectroscopy that at high temperatures as a result of the decomposition of pentaerythritol one of the reaction products is the aldehydes interacting with pentaerythritol with the formation of oligomeric compounds with a simple ether bond C-O-C. At the same time, pentaerythritol can be considered as a universal source of carbon framework for intumescent flame retardants regardless of the phosphate structure used. Originality. It has been shown that an important factor to increase the fire protection efficiency of intumescent systems is the use of polyols with an increased nucleophilicity in the esterification between polyol and phosphoric acid. Practical value. The optimal polyols as carbonizing agents for formulation of intumescent coatings with enhanced fire protection properties have been determined.